From the model to the technology of training of highly skilled medical specialist - Krivtsova, N. V.; Salekh, E. N. (Journal of Education, Health and Sport, 2018)
The article presents the experience of using the post-nonclassical model of self-realization of an individual when creating a coherent system of quality management for the preparation of competitive specialists in medicine. There was grounded the necessity of psychological support of self-organization, self-actualization and self-development of the researcher of scientific knowledge as well as in the creation of psychodimensional and human- adequate conditions of personal and professional self-improvement. Our investigation has shown that by focusing on the formation of innovative research components in the personality structure of a modern specialist, we increase the overall level of personal and professional competencies. The development of self-management abilities, the formation of a positive-differentiated attitude to new information and creative self-change, the development of skills of meaningful and intensive search for a new information space and initiative-transforming behavior in a specially organized innovation research activity under the conditions of teaching and upbringing, contribute to increasing the potential for personal self-realization of the researcher, the level of competence and maturity as well as improving the quality of the higher vocational education in general. When creating a quality management system for the organization of educational work at a medical university, it is important to take into account the nature of the relationship between the individual and the activity (structure, dynamics and level of their coherence), the specificity of the process of self-realization of the personality (form, phase and stage) as well as potential opportunities for its implementation both in the person himself, and the specificity of the educational space of the university. The presented results of the study of individual psychological characteristics of students’ personal self-realization and medical graduate students reveal the specificity of the application of technologies of educational coaching “Shlyah to Harmoniy Zhyttya” (A Way to Life Harmony) and “From Dream to Success” in the activities of the Psychological Service of the Medical University.